The performance of secondary share recommendations published in the news media and the effects on the efficiency of the Johannesburg Stock Exchange - Narendra Bhana (South African Journal of Business Management, 1990)
The objective of this study is to determine if the buy and sell recommendations published in newspapers are able to outperform the market. The empirical evidence supports the hypothesis that buy and sell recommendations released to a small group of investors is not immediately and fully reflected in the share price. Instead, it appears that subsequent publication of these recommendations in newspapers has a significant impact on the market price. The findings of this investigation are not at variance with the notion of an efficient market. The publication of analysts' recommendations in newspapers makes the market more efficient by passing on new information to a large group of investors.
Keywords: 650